Localized Amyloidosis of the Neck: A Rare Case and Literature Review - Sherwani, Rana K; Akhtar, Kafil; Afrose, Ruqaiya; Ara, Anjum (Genes Review, 2015)
Amyloidosis is the term used for a group of diseases characterized by extracellular deposition of fibrillar proteinaceous substance called amyloid, in a β- pleated sheet conformation. Amyloidoma or amyloid tumor is a tumor-like localized deposit of amyloid encountered occasionally in association with multiple myeloma, various chronic inflammatory diseases and primary amyloidosis. Soft tissue amyloidoma is rare, and soft tissue amyloidoma without evidence of systemic amyloidosis is even rarer. We report a rare case of primary AL type localized amyloidoma with a clinicopathological review and particular attention to its head and neck manifestation.